P3_10 Extinction Event - Houghton, Kate; Clark, Ashley; Simms, Henry; Kuzemczak, Jacek (Physics Special Topics, 2012)
Â This article calculates the dimensions of the crater that triggered the series of events leading to the extinction of the dinosaurs. The diameter of a crater due to an asteroid traveling at escape velocity was calculated to be 71.2 km. An incoming velocity estimate of 54.2 kms-1 was made and the crater depth is estimated to be 4.00 km using Newton's projectile penetration depth approximation.